MAINTAINING OR NEGOTIATING IDENTITY: THE SOCIO-POLITICAL DYNAMICS OF COMMUNITY MOSQUES IN MALANG, EAST JAVA, INDONESIA - Putrie, Yulia Eka; Martokusumo, Widjaja; Budi, Bambang Setia (Journal of Islamic Architecture, 2018)
The contemporary dynamics of mosque development in Indonesia is closely related to the socio-political dynamics of various Islamic groups or organizations such as Nahdlatul Ulama, Muhammadiyah, etc. A great number of mosques in Indonesia have been built by Muslim communities affiliated to one of these Islamic groups. In this case, mosque architecture can be considered as one means of expression of the communities’ specific identities which derived from their particular perspectives on the ideal picture of a mosque. However, there is also another case where a mosque is built by a heterogeneous Muslim community. In this context, the image of an ideal mosque becomes the object of negotiations among the diverse affiliated members. This paper discusses to what extent these socio-political dynamics affect the identity representation of community mosques in Malang, one of the regions in East Java where the dynamic interactions among various Islamic groups take place. The result shows that the attempts to represent identity in the community mosques are related to the socio-political dynamic of the Muslim communities. In the mosques of the specific groups, some architectural elements, such as the iconographic ornaments and colors, the spatial arrangement, and the specific features are maintained to represent their specific identities. However, in the mosques of the heterogeneous Muslim communities, these elements are negotiated and challenged by the community members. These negotiations could result, whether in the mutual understanding and tolerance, or in the space claim attempts by the dominant group through the domination of the activity systems, the role restrictions, and the physical control over the mosque.